Dutch Colonial Infrastructure Development in Takengon, 1904-1942 - Sufandi Iswanto; Nurasiah Nurasiah; T. Bahagia Kesuma (Jurnal Sejarah Citra Lekha, 2021)
The events of the Gayo-Alas War that occurred between the Gayo-Alas people against the Dutch colonial marked the end of the Aceh War. This bloody conflict also marked the Gayo Plateau region, especially Takengon, which was occupied by the Dutch colonial authorities. Since then, Takengon, which was originally just an inland region of Aceh, has begun to grow, especially its infrastructure. Therefore, this study aims to examine the infrastructure that was built in the colonial era (1904-1942). The method used in this study is the historical method, which consisted of five analytical stages, namely topic selection, heuristics, leverage, interpretation, and historiography. The results of the study show that since the Dutch colonial came to the Gayo Takengon Plateau in 1904, Takengon was more developed comparing to previous period, all of which was inseparable from infrastructure development by the Dutch colonial. Some of the infrastructures were built successfully, there were the main road between Bireuen and Takengon, central government, Dutch and Tionghoa society, market, and Dutch school.  The development of infrastructure also has had an impact for Takengon's area, such as the new society along Bireuen-Takengon highway, and the construction of Takengon-Gayo Lues' road. In addition, the opening of the road was aimed at opening the Dutch plantations and the private sector has  made the emergence of the society's settlements, like in Redelong, Pondok Baru (Janarata), Lampahan and Isaq.